Potential reactivity of granitic rocks. Petrographic characterization vs accelerated expansion tests - Ramos, V. (2017)
Several cases of alkali-silica reaction involving granitic aggregates have been diagnosed in damaged concrete structures in Portugal. Nonetheless, this kind of rock is usually regarded as slow/late reactive or even non-reactive to alkalis. Granitic rocks are widely exploited in Northern and Central Portugal, representing almost half of the produced aggregates in this country. Project IMPROVE rose from the need to accurately diagnose the potential reactivity of granites to alkalis. The study involved about forty granites collected from different regions in Portugal, from which the results of eight samples are being presented in this paper. The tests carried out include the petrographic analyses of the aggregates and mortar and concrete expansion tests. It was concluded that the content of microcrystalline quartz correlates better with the results of AAR-4.1 than with the other expansion tests.